Complete mitochondrial genome of Japanese bigeye (Pristigenys niphonia): genome characterization and phylogenetic analysis - Xu, Bo (Mitochondrial DNA B Resour, 2016)
The Japanese bigeye (Pristigenys niphonia) is a species in the genus Pristigenys and in the family Priacanthidae. To understand the phylogenetic relationship of Japanese bigeye in teleost, we firstly determined the complete mitochondrial genome of Japanese bigeye. The entire mitochondrial genome of Japanese bigeye is 16,519bp in length, including 13 protein-coding genes and 2 ribosomal RNA genes (rRNA), 22 transfer RNA genes (tRNAs), and 2 main non-coding regions. The overall base composition is 24.9% of T, 30.6% of C, 27.7% of A, and 16.8% of G. The gene arrangement, base composition, and tRNA structures of the complete mitochondrial genome of Japanese bigeye is consistent with those of other teleost. The complete mitochondrial genome of Japanese bigeye was used to construct phylogenetic tree, which shows that Japanese bigeye is clustered with the fishes of the order Perciformes. We expect that the availability of mitochondrial genome of Japanese bigeye will facilitate the further investigations of the taxonomic resolution, biogeography, and molecular systematic.